Finding Queensland in Australian cinema : poetics and screen geographies - Craven, Allison (Anthem Press, 2016)
'Finding Queensland in Australian Cinema' explores gender, race and place in selected Australian films in various phases of Australian cinema: from Charles Chauvel's 'Jedda' (1955), to the 'period' films of the New Wave in the 1970s, to the Indigenous filmmakers since the 1990s, and the contemporary era of transnational productions in Australia.
Keywords: Motion pictures -- Australia -- Queensland -- History.; Queensland -- In motion pictures.; Cinéma -- Australie -- Queensland -- Histoire.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures; Queensland; Electronic books.; History